Involvement of Eotaxins (CCL11, CCL24, CCL26) in Pathogenesis of Osteopenia and Osteoporosis - Hadis AHMADI; Hossein KHORRAMDELAZAD; Gholamhossein HASSANSHAHI; Mitra ABBASI FARD; Zahra AHMADI; Mojgan NOROOZI KARIMABAD; Majid MOLLAHOSSEINI (Tehran University of Medical Sciences, 2020)
Background: The purpose of this study was to investigate the role of eotaxin family members including C-C motif chemokine 11 (CCL11), C-C motif chemokine 24 (CCL24), and C-C motif chemokine 26 (CCL26) as the subgroups of CC-chemokine in patients affected with osteoporosis and osteopenia. Methods: Overall, 19 osteoporotic patients, 18 osteopenic individuals, and 20 healthy subjects were recruited in this study. The bone mineral density (BMD) was then measured at the lumbar spine (L1-L4) and the hip (femoral neck and total hip) using dual-energy X-ray absorptiometry for diagnosis of bone density and related disorders. Additionally, enzyme-linked immunosorbent assay (ELISA) technique was employed to measure the serum levels of CCL11, CCL24, and CCL26. Results: The circulating levels of CCL11, CCL24, and CCL26 had been increased in both groups of patients with osteopenia and osteoporosis compared to those in healthy subjects (P<0.05); while no significant difference was observed between serum levels of these chemokines in such patients. Conclusion: Eotaxins can play a role in the pathogenesis of osteoporosis and osteopenia; however, further studies are needed to clarify various roles of eotaxins in the pathophysiology of osteoporosis and osteopenia.